Debreceni zenetörténet – Az évfordulók tükrében - Duffek, Mihály (Gerundium, 2015)
MUSIC HISTORY OF DEBRECEN – IN REFLECTION OF ANNIVERSARIES. he study provides an extensive review of the 50 year history of professional music education in Debrecen. Special attention is put on the changes in the institutional structure of the training from the foundation of vocational school of music arts in 1966 to the present Music Faculty of the University of Debrecen. he writing relects not only on the spaces, forums of the daily teaching and artistic work, the living areas of the students, the international relations, but also on the important role the Faculty plays in the cultural life of the city.